Why Do Young People Sing Differently in Everyday Life Scenarios and at School? - Mito, Hiromichi (2018)
In modern society, music forms an essential part of young people’s lives (Behne, 1997; Fitzgerald, Joseph, Hayes and O’Reagan, 1995; Garton and Pratt, 1991; Larson, 1995; Larson, Kubey and Colletti, 1989). A growing body of research has revealed that young people are deeply involved in musical activities, and pop music (both listened to and sung) plays a central role in their lifestyle (Boal-Palheiros & Hargreaves, 2001; North, Hargreaves, and O’Neill, 2000; Tarrant, North, and Hargreaves, 2000). Although current youth are deeply involved in various kinds of musical activities, in modern society, involvement in musical performances is not quite as popular as just listening to music. In Japan, Masuda and Taniguchi (2005) have explained the dominance of music listening as a result of the fact that, in contemporary society, the balance of listening and performing has changed due to the development of recording technology; digitally recorded music produces vast numbers of copies, and enables people to listen to music everywhere. Barthes (1986) also pointed out that engagement in musical performance has declined in contemporary European society, in spite of a culture in the 19th century in which amateurs enjoyed performing music.